ANALYZING OF SELF-ACTUALIZATION NEEDS, REWARDS AND SOCIAL NEEDS TOWARD EMPLOYEE PERFORMANCE AT BKKBN NORTH SULAWESI PROVINCE - Sumampouw, Novena; Worang, Frederik G. (FEB Universitas Sam Ratulangi Manado, 2016)
Self-actualization needs, rewards and social needs become the major concern of management in achieving the employee performance. The objective of this study is to understand the influence of self-actualization needs, rewards, social needs toward employee performance at BKKBN north sulawesi province. The data was collected from 44 respondents of BKKBN north sulawesi province and multiple regression analysis was used as research method. The result indicated that, social needs emerged as the most influencing factor that influenced employee performance significantly, whereas the self-actualization and rewards appear to be the least important factor that influencing the employee performance because those are not influencing significantly. The author recommends to the head of institution pay more attention of the self-actualization and reward motivation in order to achieve the maximum employee performance. Keywords : employees performance, rewards, self-actualization needs, social needs